2015
DOI: 10.1128/mcb.00471-15
|View full text |Cite
|
Sign up to set email alerts
|

p110α Hot Spot Mutations E545K and H1047R Exert Metabolic Reprogramming Independently of p110α Kinase Activity

Abstract: eThe phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K) catalytic subunit p110␣ is the most frequently mutated kinase in human cancer, and the hot spot mutations E542K, E545K, and H1047R are the most common mutations in p110␣. Very little is known about the metabolic consequences of the hot spot mutations of p110␣ in vivo. In this study, we used adenoviral gene transfer in mice to investigate the effects of the E545K and H1047R mutations on hepatic and whole-body glucose metabolism. We show that hepatic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…As expected, p110α kinase activity, as assessed by the ability to add the 3’-phosphate group to phosphoinositides in p110α immunoprecipitates, was markedly decreased both in the basal- and insulin-stimulated states of the L-DKO mice compared to controls ( Figure 2A ). Overall p110β kinase activity was much lower than p110α kinase activity in control mice, consistent with previous studies 7 , 27 , and was not changed in the basal state between controls and L-DKO mice ( Figure 2B ). However, p110β kinase activity was significantly decreased in the insulin-stimulated state of the L-DKO mice ( Figure 2B ), even though similar amounts of p110β protein were associated with IRS1 in controls and L-DKO mice ( Figure 1K and 1M ).…”
Section: Resultssupporting
confidence: 91%
“…As expected, p110α kinase activity, as assessed by the ability to add the 3’-phosphate group to phosphoinositides in p110α immunoprecipitates, was markedly decreased both in the basal- and insulin-stimulated states of the L-DKO mice compared to controls ( Figure 2A ). Overall p110β kinase activity was much lower than p110α kinase activity in control mice, consistent with previous studies 7 , 27 , and was not changed in the basal state between controls and L-DKO mice ( Figure 2B ). However, p110β kinase activity was significantly decreased in the insulin-stimulated state of the L-DKO mice ( Figure 2B ), even though similar amounts of p110β protein were associated with IRS1 in controls and L-DKO mice ( Figure 1K and 1M ).…”
Section: Resultssupporting
confidence: 91%
“…Overall p110β kinase activity was much lower than p110α kinase activity in control mice, consistent with previous studies 7, 27 , and was not changed in the basal state between controls and L-DKO mice ( Figure 2B). However, p110β kinase activity was significantly decreased in the insulin-stimulated state of the L-DKO mice ( Figure 2B), even though similar amounts of p110β protein were associated with IRS1 in controls and L-DKO mice ( Figure 1K and 1M).…”
Section: Resultssupporting
confidence: 91%
“…Indeed, we found that the platelet p110α phenotype could not be mimicked by the presence of the p110α inhibitor PIK-75. Kinase-independent functions of p110α have recently been described in cells with gain-of-function mutations in the p110α gene (PIK3CA; hot spot mutations in E545K/H1047R) [51]. Lipid kinase-independent functions have also been demonstrated for the Class I PI3K isoforms p110β and p110δ, which contribute to insulin signalling and cell survival respectively [52,53].…”
Section: Discussionmentioning
confidence: 99%